L-arginine metabolism as pivotal interface of mutual host–microbe interactions in the gut - Nüse, Björn; Holland, Tim; Rauh, Manfred; Gerlach, Roman; Mattner, Jochen (Gut Microbes, 2023)
L-arginine (L-arg) is a versatile amino acid and a central intestinal metabolite in mammalian and microbial organisms. Thus, L-arg participates as precursor of multiple metabolic pathways in the regulation of cell division and growth. It also serves as a source of carbon, nitrogen, and energy or as a substrate for protein synthesis. Consequently, L-arg can simultaneously modify mammalian immune functions, intraluminal metabolism, intestinal microbiota, and microbial pathogenesis. While dietary intake, protein turnover or de novo synthesis usually supply L-arg in sufficient amounts, the expression of several key enzymes of L-arg metabolism can change rapidly and dramatically following inflammation, sepsis, or injury. Consequently, the availability of L-arg can be restricted due to increased catabolism, transforming L-arg into an essential amino acid. Here, we review the enzymatic pathways of L-arg metabolism in microbial and mammalian cells and their role in immune function, intraluminal metabolism, colonization resistance, and microbial pathogenesis in the gut.
CRIS-Team Scopus Importer:2023-07-21
Keywords: colonization resistance; dietary L-arg supplementation; host–microbe interaction; intestinal microbiota; L-arginine (L-arg); microbial pathogenesis; mucosal immune function; mutual metabolic pathways; virulence factor